KINETIC AND ISOTHERMAL STUDY OF BIOSORPTION OF ZINC (II) AND CADMIUM (II) FOR A SYSTEM MONOMETALLIC-BIMETALLIC BY UNDARIA PINNATIFIDA SP. - Mori C., M. (2013)
Adsorption capacity was studied having seaweed Undaria pinnatifida sp. in adsorption of metal ions of zinc and cadmium to an individual system (monometallic) and mixtures (bimetal) of an aqueous solution. We studied this process preliminarily, contact time, pH of the biopolymer solution and treatment. The kinetic study of the behavior determined that the adsorption system was pseudo second-order equation using the Langergren (initial concentration 50mg/L, weight = 0,4g biopolymer, pH = 3 - 5). The nonlinear modeling the Langmuir and Freundlich isotherm, the Langmuir model obtained a better correlation coefficient close to unity, determining the maximum sorption capacity of metals such as zinc ions was qmax = 44,91mg/g and cadmium qmax = 102,38 mg/g at pH = 4 at a contact time of 60 minutes, with the alga in untreated monometallic system, being more efficient for the ion adsorption cadmium. For bimetallic systems used two methods, the method disclosed isoconcentrations that the adsorption behavior of both metals in solution and method of varying concentrations employing the regression analysis model modified Langmuir unveiled values of the maximum adsorption capacity, while for the zinc metal ion qmax = 0,27 mmol/g, cadmium qmax = 1,27 mmol/g for the adsorption of both metals on biomass qmax = 1,13 mmol/g.